The characteristics and risk factors of human papillomavirus infection: an outpatient population-based study in Changsha, Hunan - Bingsi Gao (Nature Portfolio, 2021)
Abstract This cross-sectional study investigated the characteristics of cervical HPV infection in Changsha area and explored the influence of Candida vaginitis on this infection. From 11 August 2017 to 11 September 2018, 12,628 outpatient participants ranged from 19 to 84 years old were enrolled and analyzed. HPV DNA was amplified and tested by HPV GenoArray Test Kit. The vaginal ecology was detected by microscopic and biochemistry examinations. The diagnosis of Candida vaginitis was based on microscopic examination (spores, and/or hypha) and biochemical testing (galactosidase) for vaginal discharge by experts. Statistical analyses were performed using SAS 9.4. Continuous and categorical variables were analyzed by t-tests and by Chi-square tests, respectively. HPV infection risk factors were analyzed using multivariate logistic regression. Of the total number of participants, 1753 were infected with HPV (13.88%). Females aged ≥ 40 to < 50 years constituted the largest population of HPV-infected females (31.26%). The top 5 HPV subtypes affecting this population of 1753 infected females were the following: HPV-52 (28.01%), HPV-58 (14.83%), CP8304 (11.47%), HPV-53 (10.84%), and HPV-39 (9.64%). Age (OR 1.01; 95% CI 1–1.01; P < 0.05) and alcohol consumption (OR 1.30; 95% CI 1.09–1.56; P < 0.01) were found to be risk factors for HPV infection. However, the presence of Candida in the vaginal flora was found to be a protective factor against HPV infection (OR 0.62; 95% CI 0.48–0.8; P < 0.001). Comparing with our previous study of 2016, we conclude that the subtype distribution of HPV infection is relatively constant in Changsha. Our data suggest a negative correlation between vaginal Candida and HPV, however, more radical HPV management is required in this area for perimenopausal women and those who regularly consume alcohol.